The COVID Complex: A Review of Platelet Activation and Immune Complexes in COVID-19 - Jevtic, Stefan D.; Nazy, Ishac (Frontiers in Immunology, 2022)
Coronavirus disease 2019 (COVID-19) is a highly prothrombotic viral infection that primarily manifests as an acute respiratory syndrome. However, critically ill COVID-19 patient will often develop venous thromboembolism with associated increases in morbidity and mortality. The cause for this prothrombotic state is unclear but is likely related to platelet hyperactivation. In this review, we summarize the current evidence surrounding COVID-19 thrombosis and platelet hyperactivation. We highlight the fact that several studies have identified a soluble factor in COVID-19 patient plasma that is capable of altering platelet phenotype in vitro. Furthermore, this soluble factor appears to be an immune complex, which may be composed of COVID-19 Spike protein and related antibodies. We suggest that these Spike-specific immune complexes contribute to COVID-19 platelet activation and thrombosis in a manner similar to heparin-induced thrombocytopenia. Understanding this underlying pathobiology will be critical for advancement of future research and therapeutic options.